Hubungan Karakteristik dan Motivasi Petani dalam Alih Fungsi Lahan Sawah menjadi Lahan Pertambangan Emas Tanpa Izin - Susridar (LP3M Universitas Putra Bangsa, 2024)
Rice fields have a very important meaning in efforts to maintain food security, but with the times, population growth and economic demands, the existence of food fields is starting to be disturbed. One of the serious problems currently related to food land is the increasingly widespread conversion of food land to other uses. The land that is converted is generally agricultural land because the land rent for agricultural land is relatively lower when compared to land rent for non-agricultural use. Agricultural land that has been converted includes paddy fields and dry land, the conversion of rice fields to technically irrigated land is a real threat to the resilience of food self-sufficiency. The causes of land conversion include: population growth and residential development, industrialization, construction of road facilities and economic factors. Based on these causes, this research aims to 1) determine the relationship between the characteristics and motivation of farmers in converting rice fields into gold mining land without permits in Pangkalan Jambu District, Merangin Regency; 2) To determine the relationship between farmers' motivation factors and the decision to convert land into gold mining without a permit in Pangkalan Jambu District, Merangin Regency.